Innovation Infrastructure: Notion, Classification, Functionality - E. I. Kushnikov (Вестник Российского экономического университета имени Г. В. Плеханова)
Persuasion of state innovation policy and the necessity to attain long-term land-marks of scientific and technological development require modernization and efficient use of innovation infrastructure. However, legislative definition of this notion is characterized by certain drawbacks that are highlighted by academic community. Innovation infrastructure can be understood not only as a sum total of its entities, but as a section of environment (for instance, national, innovative) through structural – functional and institutional approaches. Legislative definition of innovation infrastructure eliminates from the law field a number of business entities participating in service function for Russian innovators. In view of this it is proposed to introduce changes in legislative definition in the part of specification of entities and projects. Discussions and novelties also deal with classifications and innovation infrastructure, its functional purpose, in spite of the fact that more than a decade has passed since the moment of defining and legislative fixing of classification. At the same time we can observe attempts to disfigure the role of innovation infrastructure connected with rendering services to innovators, which could hinder innovation processes in the country. In this case it is proposed to push off from the need to take into account auxiliary functions at each stage of life cycle of innovation project in order to support timely innovators on their way to successful market implementation of their projects.